Evaluation of long-term clinical outcomes among PPIUCD users at six medical college hospitals - Radhika, A. G.; Gupta, Rashmi; Suneja, Amita; Dorairajan, Gowri; Aggarwal, Pratima; Ashok, Venkatesh; Suri, Vanita; Singla, Rimpi; Nanda, Smiti; Chauhan, Meenakshi; Rani, Vandana; Arora, Nalini; et al. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Postpartum IUCDs are becoming increasingly popular in low-income countries, but there are few studies addressing long-term outcomes. Methods: A prospective observational study conducted in six tertiary care hospitals across India to investigate satisfaction rates, expulsions, adverse events and complications of PPIUCD for up to 24 months. Results: PPIUCD was accepted by 16262 out of 56619 eligible women. Of these, 59.6% had NVDs, and the rest had LSCSs. PPIUCD continuation proportion was 90.3% at 6 weeks and 72.5% at 6 months. It decreased to 50.6% after 24 months. Women reported 73.91% satisfaction at 6 months, but only 48% at 24 months. PPIUCD removal and expulsion rates were 8.39% and 3.76% at 6 months and 13.4% and 2.95% at 24 months. Removal rates were significantly different between NVD and LSCS women (25.37% versus 18.8%; p<0.001). Thread discomfort was the most common reason for removal and was more common in LSCS group. Expulsions were higher at six months in the NVD, 9.85% versus 7.10% (p<0.001). Reported side effects were abdominal pain, abnormal bleeding and white discharge in both groups. Conclusions: There was a progressive reduction in continuation and satisfaction with PPIUCD use over 24 months. Thread discomfort, abdominal pain, and abnormal bleeding were major reasons for dissatisfaction. Most of the women chose private practitioners for IUCD. Additionally, the reported side effects highlight the need for further research. Both quality of life and contraceptive efficacy play a major role in the success of contraception.